(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This paper presents the important results of the soil analysis of the Taj Baj pond bottom of Hajipur, North Bihar during the session 2019-2020. Pond soil samples of Hajipur (North Bihar) have been analysed regarding their suitability for useable purpose. The samples were analysed after every three months for various parameters like pH, organic carbon, Phosphate, Ca & Mg, Carbonate and Bicarbonate.